2014
DOI: 10.4103/1817-1745.139262
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence after discontinuation of antiepileptic drug therapy in children with epilepsy

Abstract: Objectives:The numerous antiepileptic drug (AED) withdrawal studies published in the last 40 years have relied mainly on heterogeneous study groups. There is still no general agreement on the criteria to predict safe discontinuation. The goal of this study was to assess the outcome of AED withdrawal in epileptic children.Materials and Methods:Three hundred and eight children with epilepsy were enrolled, and these patients followed at least 1 year after drug withdrawal. Time to seizure relapse and predictive fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
14
3
2
Order By: Relevance
“…A family history of epilepsy was reported as a risk factor for recurrence in patients with idiopathic epilepsy by Shinnaret al [15]. We did notfind it to be a risk factor for recurrence, which is consistent with some studies [10,27]. A history of febrile convulsions has been reported previously not to be a recurrence riskfactor, as in our study [9,10,16].…”
Section: Number Of Patients(%)supporting
confidence: 92%
See 3 more Smart Citations
“…A family history of epilepsy was reported as a risk factor for recurrence in patients with idiopathic epilepsy by Shinnaret al [15]. We did notfind it to be a risk factor for recurrence, which is consistent with some studies [10,27]. A history of febrile convulsions has been reported previously not to be a recurrence riskfactor, as in our study [9,10,16].…”
Section: Number Of Patients(%)supporting
confidence: 92%
“…But there are also controversial studies [8,27]. Cognitive impairment has been found to be a significant risk factor for recurrence [17,27], but in our study no correlation was found as in previous studies [8,10,29]. Conflicting results have been reported about the role of abnormalities on EEG in predicting recurrence.…”
Section: Number Of Patients(%)contrasting
confidence: 73%
See 2 more Smart Citations
“…3,4,25 In terms of EEG, abnormal EEG findings have been reported to have a modest impact on recurrence. 16,26,27 However, the EEG variable was not identified as a prognostic covariate in this study.…”
Section: Discussionmentioning
confidence: 58%